Influence of core box vents distribution on flow dynamics of core shooting process based on experiment and numerical simulation - Ni, Chang-jiang; Lu, Gao-chun; Zhang, Qing-dong; Jing, Tao; Wu, Jun-jiao; Yang, Lin-long; Wu, Qin-fang (China foundry, 2016)
Core shooting process plays a decisive role in the quality of sand cores, and core box vents distribution is one of the most important factor determining the effectiveness of core shooting process. In this paper, the influence of core box vents distribution on the flow dynamics of core shooting process was investigated based on in situ experimental observations with transparent core box, high-speed camera and pressure measuring system. Attention was focused on the variation of both the flow behavior of sand and pressure curves due to different vents distribution. Taking both kinetic and frictional stress into account, a kinetic-frictional constitutive model was established to describe the internal momentum transfer in the solid phase. Two-fluid model （TFM） simulation was then performed and good agreement was achieved between the experimental and simulated results on both the flow behavior of sand and the pressure curves. It was found that vents distribution has direct effect on the pressure difference of different locations in the core box, which determines the buoyancy force exerting on the sand particles and significantly influences the filling process of core sand.